Structures of Surfactant System Studied by Positron Annihilation Lifetime Spectroscopy - Ibrahim, Rosdi (1996)
Surfactant system has many applications in industry. Many investigations have been carried out on surfactants using various methods such as small-angle neutron scattering (SANS), small-angle x-ray scattering(SAXS),conductivity freeze-fracture electron microscopy and nuclear magnetic resonance(NMR).In the positron annihilation lifetime spectroscopy technique, the lifetime ('t2)of positron that interacts with surfactant medium is measured using fast coincidence system. The intensity of formation of orthopositronium(12), when positron interact with aggregate of surfactant system are sensitive to phase changes. In amphiphilic system with bicontinous character geometry of periodic phase can be explained using minimal surfaces. Factors influencing the topology includes the length of surfactant and cosurfactant tails and the aqueous volume fraction. Positron are readily attracted to these centres. Changes in the geometry of the interfacial layer thus will influence the lifetime and intensity of the orthopositronium atom formed. These parameters are obtainable using the POSITR ON FIT programme. In this study, three surfactant systems were investigated. Firstly, the intensity (12) and lifetime ("(2) of the Didodecyl DimethylAmmonium Bromide (ODAB) - Water - Octane system were measured at various amount of water content in the surfactant system in the diamond and body centred cubic phases. A symmetry transitions from diamond phase to body-centred cubic phase was observed in this system.